Antitumor and immunomodulating activities of the polysaccharide fractions from Artemisia selengensis and Artemisia iwayomogi - Koo, K.A.; Kwak, J.H.; Lee, K.R.; Zee, O.P.; Woo, E.R.; Park, H.K.; Youn, H.J. (1994)
Effects of the polysaccharide fractions purified from Artemisia selengensis and Artemisia iwayomogi on the immune system was studied. The polysaccharide fractions, respectively called ASP1 and AIP1, may interact with macrophages and lymphocytes in spleen, increasing the population of those cell types in vivo and in vitro. Both ASP1 and AIP1 fractions also suppress transplanted tumor cell growth and augment antibody production. This study suggests that ASP1 and AIP1 fractions may have immunomodulating and antitumor activities. ？ 1994, The Pharmaceutical Society of Korea. All rights reserved.